Income Smoothing: An Experiment. - Koch, Bruce S. (The Accounting Review, 1981)
ABSTRACT: This study consists of a laboratory experiment that examines the income smoothing process with respect to motivation (reflected by the cost of smoothing), type of smoothing variable (real or artificial) and management structure (diverse or concentrated ownership). The results indicate that less smoothing occurs when the cost of smoothing is higher, that there is more smoothing when ownership is diverse than when ownership is not diverse, and that smoothing is greater with the use of artificial (accounting) variables than with real (transactional) variables. The data were analyzed using analysis of variance of repeated observations. All results are significant beyond the .001 level. The conclusions relating to ownership are consistent with existing literature.